1980
DOI: 10.1159/000122967
|View full text |Cite
|
Sign up to set email alerts
|

H<sub>1</sub>- and H<sub>2</sub>-Histamine Receptor Antagonists and Induced Release of Prolactin in Male Rats

Abstract: The effects of 3rd ventricle injection of metiamide, an H2-histamine receptor antagonist and pyrilamine, an H1-histamine receptor antagonist, on the increase of plasma prolactin induced by two doses of histamine in normal male rats were studied. Metiamide did prevent the stimulating action of histamine whereas pyrilamine was not effective. Histamine-induced prolactin release was also blocked by low doses of the 2 antihistamines given in combination. Metiamide per se has no effect but high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
1

Year Published

1982
1982
1991
1991

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 6 publications
3
12
1
Order By: Relevance
“…It was shown in a previous paper that the histamine-in duced prolactin release in male rats is blocked by Hz-antihistamine, metiamide [10]. The present results support this finding, and show in addition that ranitidine, a novel H2-histamine agonist [4], has a similar action.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It was shown in a previous paper that the histamine-in duced prolactin release in male rats is blocked by Hz-antihistamine, metiamide [10]. The present results support this finding, and show in addition that ranitidine, a novel H2-histamine agonist [4], has a similar action.…”
Section: Discussionsupporting
confidence: 90%
“…In our experi ence [10; and the present results] both antihistamines, when given alone intraventricularly did not affect prolactin re lease. On the other hand, mepyramine as observed herein and previously [10] did not prevent the histamine effect. As is known, mepyramine is a potent Hi-antagonist [31].…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The stimula tory effect is mediated via activation of HA receptors, but different results have been obtained regarding the specific type of HA receptor (Hi-or H2-receptor) involved. Some investigators reported that the PRL-releasing effect of ICV administered HA to male rats is mediated via H^-receptors, Received: August 7, 1985 Accepted after revision: March 10, 1986 since the response was blocked by H^-receptor antagonists administered ICV but not by H|-receptor antagonists ad ministered ICV or systemically [3,4,19].Other investigators found that HA stimulated PRL se cretion via Hi-receptors and inhibited the secretion via H2-receptors (I, 12, 14, 20]. Thus, in lactating rats the sucklinginduced PRL release was inhibited by ICV and IV adminis tration of Hi-receptor antagonists, whereas the response was not affected by ICV or IV infusion of an Hi-receptor antagonist [1].…”
mentioning
confidence: 99%